LEAF PHARMACOGNOSY OF SENNOSOID YIELDING HERB SENNA OCCIDENTALIS (L.) LINK FROM THE LATERITIC ZONE OF SOUTHERN WEST BENGAL, INDIA - SK MD ISMAIL AL AMIN; ASIS KUMAR NANDI (International Journal of Pharma and Bio Sciences, 2014)
Senna occidentalis (L.) Link, of the family Caesalpiniaceae and locally known as ‘kalkasundha’ in India, is a medicinal plant of multifarious uses. Right from it’s earliest mentioning in ayurveda along with other earlier records claim its use as analgesic, antipyretic drug, to treat colitis, constipation, dysentery, jaundice, cholera, leprosy and many others. Its antibacterial, antifungal, antimutagenic, anti-tumour and hepatoprotective properties depends on host of chemicals like, achrosin, aloe-emodin, emodin, anthraquinones, anthrones, sennosoid G, D, C, B, A, isorhein, rhein, kaempferein etc. The plant product in raw and processed form is marketed by different companies. Pharmaceutical information help identify a species, even when plant parts are pounded to powder form. This information also proves to be invaluable as it comes to use in detecting spurious materials, mixed as an adulterant, from the original ones. The present study displays various characteristics of the species, the combination of which will be unique for it and of pharmacognostic significance.